ÐÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ðµ Ð¾Ð±Ð¾ÑÐ½Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð²Ð¾Ð·Ð¼Ð¾Ð¶Ð½Ð¾ÑÑ‚Ð¸ ÐºÐ¾Ð¼Ð±Ð¸Ð½Ð°Ñ†Ð¸Ð¸ Ð°Ð»Ð»Ð¾- Ð¸ Ð³ÐµÑ‚ÐµÑ€Ð¾Ð¿Ð»Ð°ÑÑ‚Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ð¼Ð°Ñ‚ÐµÑ€Ð¸Ð°Ð»Ð¾Ð² Ð¿Ñ€Ð¸ Ð²Ð¾ÑÑÑ‚Ð°Ð½Ð¾Ð²Ð»ÐµÐ½Ð¸Ð¸ Ð¿ÐµÑ€ÐµÐ´Ð½ÐµÐ¹ Ð±Ñ€ÑŽÑˆÐ½Ð¾Ð¹ ÑÑ‚ÐµÐ½ÐºÐ¸ - Militsa, K. N.; Sorokina, I. V.; Gorgol, N. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
It has been experimentally established that application of cryopreserved chorial membrane (CCM) inhibits the formation of adhesive fusion between omentum and intestinal loops and between chorial and intestinal serous membrane within postoperative period. It has been noted that CCM has the role of barrier, suppressing penetration of infection and inflammation progression in it.